THE INTERACTION FORMS BUCKLING OF COMPRESSED THIN-WALLED CHANNEL WITH PRIOR LOCAL SWELLING - Raksha, S. V. (Science and Transport Progress, 2009)
The coupled instability of thin-walled columns with a preliminary local buckling is considered taking into account the overall initial imperfection, eccentricity of the compression force application and interaction of overall and local buckling modes.